Clinicopathological Features of Ocular Adnexal Mantle-Cell Lymphoma in an International Multicenter Cohort - Knudsen, Marina K. H. (JAMA Ophthalmol, 2017)
IMPORTANCE: To our knowledge, the clinical features of ocular adnexal mantle-cell lymphoma (OA-MCL) have not previously been evaluated in a large multicenter cohort. OBJECTIVE: To characterize the clinical features of OA-MCL. DESIGN, SETTING, AND PARTICIPANTS: This retrospective multicenter study included patient data collected from January 1, 1980, through December 31, 2015, at 6 eye cancer centers in 4 countries. Medical records of 55 patients with OA-MCL were reviewed; the median length of follow-up was 33 months. MAIN OUTCOMES AND MEASURES: Overall survival, disease-specific survival, and progression-free survival were the primary end points. RESULTS: Fifty-five patients were included; ocular adnexal MCL was found to be most common in older individuals (mean age, 70 years) and men (n = 42 of 55; 76%). Patients with OA-MCL frequently presented with disseminated lymphoma (n = 34 of 55; 62%), and were likely to experience stage IVE disease (n = 35 of 55; 64%), with bilateral involvement (n = 27 of 55; 47%), tumor masses (n = 27 of 36; 75%), and involvement of the orbit (n = 32 of 55; 58%). Chemotherapy with or without external beam radiation therapy was the most frequently used treatment. Overall survival rates for the entire cohort were 65% at 3 years (95% CI, 52%-78%) and 34% at 5 years (95% CI, 21%-47%). Disease-specific survival after 5 years was 38% for the entire cohort (95% CI, 25%-51%); the disease-specific survival adjusted by eye cancer center was better in patients who had received rituximab in addition to the chemotherapy regimen (hazard ratio, 3.3; 95% CI, 1.0-14.7; P = .06). The median progression-free survival was 2.3 years (95% CI, 1.8-2.7 years) in patients who experienced recurrence after primary treatment, and 4.1 years (95% CI, 3.9-4.3 years) in patients who presented with a relapse of systemic lymphoma in the ocular adnexal region. CONCLUSIONS AND RELEVANCE: These results suggest that the distinctive features of OA-MCL are its appearance in older male individuals, advanced stage and bilateral manifestation at the time of diagnosis, and aggressive course. The prognosis of patients with OA-MCL might be improved by addition of rituximab to chemotherapy treatment.